у = 1/2 х + 1, если х = -4, -2, -1, 0, 1, 2, 4
1) у = 1/2 * (-4) + 1 = -2 + 1 = -1; 2) у = 1/2 * (-2) + 1 = -1 + 1 = 0; 3) у = 1/2 * (-1) + 1 = -1/2 + 1 = 1/2; 4) у = 1/2 * 0 + 1 = 0 + 1 = 1; 5) у = 1/2 * 1 + 1 = 1/2 + 1 = 1 ц 1/2; 6) у = 1/2 * 2 + 1 = 1 + 1 = 2; 7) у = 1/2 * 4 + 1 = 2 + 1 = 3;
1)y=1/2х+1,если х=-4
у=1/2*(-4)+1
у=-3
2)у=1/2х+1,если х=-2
у=1/2*(-2)+1
у=0
3)у=1/2х+1,при х=-1
у=1/2*(-1)+1
у=1/2
4)у=1/2х+1,при х=0
у=1/2*0+1
у=1
5)у=1/2х+1,при х=1
у=1/2*1+1
у=3/2
6)у=1/2х+1,при х=2
у=1/2*2+1
у=2
7)у=1/2х+1,при х=4
у=1/2*4+1
у=3